The Principle of Mabda' Ar-Rada'iyyah in Land Purchase Agreements with Fraud Elements in State Court Judgment Number 12/Pdt.G/2017/PN.Mlg - Dwi Fidhayanti; Illa Miftachul Jannah (Institut Agama Islam Negeri Palangka Raya, 2022)
Court Judgment Number 12/Pdt.G/2017/PN.Mlg became a decision on Kartono's request to cancel the land sale and purchase agreement because it contained elements of fraud. The purpose of this study is to analyze the principle of mabda' ar-rada'iyyah in the land sale and purchase agreement with an element of fraud in Court Judgment Number 12/Pdt.G/2017/PN.Mlg. Types of normative juridical research with a statutory approach and a case approach. Primary, secondary and tertiary legal materials are analyzed using descriptive qualitative methods. The results of this study indicate that based on the request for annulment of the agreement submitted by Kartono which was granted by the Panel of Judges, it resulted in the cancellation of the land sale and purchase agreement and returned to the original owner, namely Kartono. The agreement violated subjective requirements because the sale and purchase contained elements of persuading, influencing, and deceiving or using false prestige towards Kartono during the land purchase process. This agreement does not fulfill the principle of mabda' ar-rada'iyyah, because the agreement/will to enter into the agreement was given on the basis of an element of fraud committed by the buyer, causing the agreement to be void/invalid.Court Judgment Number 12/Pdt.G/2017/PN.Mlg became a decision on Kartono's request to cancel the land sale and purchase agreement because it contained elements of fraud. The purpose of this study is to analyze the principle of mabda' ar-rada'iyyah in the land sale and purchase agreement with an element of fraud in Court Judgment Number 12/Pdt.G/2017/PN.Mlg. Types of normative juridical research with a statutory approach and a case approach. Primary, secondary and tertiary legal materials are analyzed using descriptive qualitative methods. The results of this study indicate that based on the request for annulment of the agreement submitted by Kartono which was granted by the Panel of Judges, it resulted in the cancellation of the land sale and purchase agreement and returned to the original owner, namely Kartono. The agreement violated subjective requirements because the sale and purchase contained elements of persuading, influencing, and deceiving or using false prestige towards Kartono during the land purchase process. This agreement does not fulfill the principle of mabda' ar-rada'iyyah, because the agreement/will to enter into the agreement was given on the basis of an element of fraud committed by the buyer, causing the agreement to be void/invalid.